Pulmonary surfactant protein A and surfactant lipids upregulate IRAK-M, a negative regulator of TLR-mediated inflammation in human macrophages - Nguyen, Huy A. (American Physiological Society, 2012)
Alveolar macrophages (AMs) are exposed to frequent challenges from inhaled particulates and microbes and function as a first line of defense with a highly regulated immune response because of their unique biology as prototypic alternatively activated macrophages. Lung collectins, particularly surfactant protein A (SP-A), contribute to this activation state by fine-tuning the macrophage inflammatory response. During short-term (10 min–2 h) exposure, SP-A's regulation of human macrophage responses occurs through decreased activity of kinases required for proinflammatory cytokine production. However, AMs are continuously exposed to surfactant, and the biochemical pathways underlying long-term reduction of proinflammatory cytokine activity are not known. We investigated the molecular mechanism(s) underlying SP-A- and surfactant lipid-mediated suppression of proinflammatory cytokine production in response to Toll-like receptor (TLR) 4 (TLR4) activation over longer time periods. We found that exposure of human macrophages to SP-A for 6–24 h upregulates expression of IL-1 receptor-associated kinase M (IRAK-M), a negative regulator of TLR-mediated NF-κB activation. Exposure to Survanta, a natural bovine lung extract lacking SP-A, also enhances IRAK-M expression, but at lower magnitude and for a shorter duration than SP-A. Surfactant-mediated upregulation of IRAK-M in macrophages suppresses TLR4-mediated TNF-α and IL-6 production in response to LPS, and IRAK-M knockdown by small interfering RNA reverses this suppression. In contrast to TNF-α and IL-6, the surfactant components upregulate LPS-mediated immunoregulatory IL-10 production, an effect reversed by IRAK-M knockdown. In conclusion, these data identify an important signaling regulator in human macrophages that is used by surfactant to control the long-term alveolar inflammatory response, i.e., enhanced IRAK-M activity.